2015
DOI: 10.1111/ases.12186
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal submucosal mass as presentation of intestinal endometriosis

Abstract: Submucosal lesions are mass-like protuberances into the gastrointestinal lumen covered by normal mucosa. Making a definitive diagnosis is difficult because of the number of benign and malignant lesions and extrinsic compression. Here we report the case of a 42-year-old woman referred for colon polypectomy. Colonoscopy revealed a polypoid formation with externalization from the appendicular orifice covered by normal mucosa and another formation at the sigmoid colon. The histopathology of both lesions was normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
1
0
4
Order By: Relevance
“…Los estudios baritados, como el colon por enema, también pueden ser de ayuda, pero con menor sensibilidad y especificidad diagnóstica. En cuanto a las pruebas de laboratorio, el CA-125 puede ser útil para confirmar la endometriosis 10,11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los estudios baritados, como el colon por enema, también pueden ser de ayuda, pero con menor sensibilidad y especificidad diagnóstica. En cuanto a las pruebas de laboratorio, el CA-125 puede ser útil para confirmar la endometriosis 10,11 .…”
Section: Discussionunclassified
“…El tratamiento quirúrgico de la endometriosis es controvertido, no obstante, en la variante intestinal, donde hay invasión colorrectal sin respuesta al manejo médico, existe la alternativa del tratamiento quirúrgico en conjunto con ginecología, realizando resecciones intestinales por vía laparoscópica 11 .…”
Section: Discussionunclassified
“…Although no reports on menstrual and nonmenstrual imaging have been found in previous reports, the accumulation of future cases is considered important. Obtaining a preoperative diagnosis appears to be difficult for patients with a submucosal lesion; however, Oliveira et al reported that intestinal endometriosis should be considered in the differential diagnosis of patients with submucosal tumors of the colon [4]. If intestinal endometriosis is established as part of the differential diagnosis, a preoperative diagnosis should not be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Ecografia abdominală este raportată ca un instrument de diagnostic important pentru IA și este considerată metoda de alegere pentru copiii cu semne sugestive [8,30,46,72,90]. Indiciu precum aspectul "țintă" (cunoscut și sub denumirea de "gogoașă" sau "a ceapei") cu semne inelare hiperecogene și hipoecogene multiconcentrice reprezentând un apendicele invers și un mezoapendice pe ecografiile axiale (transversale) au fost descrise în literatura de specialitate ca vizualizare imagistică clasică pentru IA [4,8,9,30,42,43,64,70,86]. Mai mult decât atât, un apendice vermiform inversat care pătrunde în cec asemănător cu deget poate fi observat pe sonogramele longitudinale [9].…”
Section: Aspect Diagnosticunclassified
“…Rezecție extinsă, cum ar fi rezecția ileocecală pe cale deschisă sau cea laparoscopică cu anastomoză ileocolică [23,25,26,31,35,43,45,59] sau hemicolectomie pe dreaptă [26,30,31,35,41,51,55,70] ar trebui să fie întreprinsă în cadrul neoplasmului (de exemplu, invaginare completă a apendicelui vermiform peste 2,0 cm aproape de valva ileocecală) [93]. Această abordare permite obținerea unei marje adecvate fără tumori [48].…”
Section: Managementulunclassified